The effects of dipeptidyl peptidase-4 inhibitors on bone fracture among patients with type 2 diabetes mellitus: A network meta-analysis of randomized controlled trials. - Jun Yang; Chao Huang; Shanshan Wu; Yang Xu; Ting Cai; Sanbao Chai; Zhirong Yang; Feng Sun; Siyan Zhan (PLoS ONE)
Aim The association between dipeptidyl peptidase-4 inhibitors (DPP-4is), a class of anti-diabetes, and bone fracture in patients with type 2 diabetes mellitus (T2DM) is unknown. This meta-analysis aimed to systematically evaluate the effects of DPP-4is on bone fracture in T2DM patients. Methods We searched the Cochrane Library, Embase, Medline and ClinicalTrials.gov from inception through April 28th, 2016 to identify randomized controlled trials (RCTs) that compared DPP-4is with placebo or other anti-diabetes in T2DM patients. RCTs lasting more than 12 weeks and having data on bone fracture were included. We conducted random-effects meta-analysis to estimate odds ratios (ORs) and their 95% confidence intervals (CIs), and network meta-analysis (NMA) to supplement direct comparisons. Predictive interval plot and node-splitting method were used to evaluate the heterogeneity and inconsistency for NMA, while the funnel plot was applied to explore publication bias. Besides, study quality was assessed according to Cochrane risk of bias tool. Results We identified 75 RCTs with a total of 70,207 patients and 11 treatments: interventions included 5 DPP-4is (alogliptin, linagliptin, saxagliptin, sitagliptin, vildagliptin), while controls included placebo and 5 other anti-diabetes (sulfonylureas, glucagon-like peptide-1 receptor agonists, metformin, thiazolidinediones, sodium-glucose co-transporter 2 inhibitors). In the NMA, the risk of fracture for alogliptin tended to decrease when versus placebo (OR, 0.51; 95% CI, 0.29 to 0.88). Besides, aloglitpin had a lower risk compared with linagliptin (OR, 0.45; 95% CI, 0.20 to 0.99) and saxagliption (OR, 0.46; 95%CI, 0.25 to 0.84); the risk was higher with saxagliptin when versus sitagliptin (OR, 1.90; 95% CI, 1.04 to 3.47) and sulfonylureas (OR, 1.98; 95% CI, 1.06 to 3.71). In the direct pairwise meta-analysis, alogliptin was associated with a non-significant tendency to reduction of bone fracture compared with placebo (OR, 0.54; 95% CI, 0.29 to 1.01). Ranking probability analysis indicated alogliptin decreased the risk of bone fracture most with a probability of 76.3%. Conclusion Alogliptin may be associated with a lower risk of bone fracture compared with placebo, linagliptin, or saxagliptin, while other anti-diabetes did not seem to have an association with the risk of bone fracture.